INFLUENCE OF SURFACE DEFECTS, INHERITED FROM ROLLED WIRE, ON QUALITY OF A COLD-DRAWN WIRE - A. N. Savenok; T. P. Kurenkova; I. V. Borisovets; A. A. Saharnaja (Литьë и металлургия, 2012)
Researches of the most often occurred surface defects of rolled wires, their modification at drawing and influence on technological process and quality of cold-drawn wire with regard to working conditions of hardware shops of OAO “BMZ” are  presented.